Image Steganography and Steganalysis : A Survey (International Journal of Scientific Research and Management (IJSRM), 2014)
Steganography is communication of secret data in an appropriate carrier, e.g. image, audio, video or TCP/IP header file. For hiding secret data in digital images, large varieties of steganographic techniques are available; some are more complex than others. And all of them have their respective pros and cons. This paper intends to give understanding and evolution of different existing digital image steganography techniques of data hiding in spatial, transform and compression domains. It integrates research work on steganography and steganalysis. Detection of steganography, estimation of message length, and its extraction are part of the field of steganalysis. The battle between steganography and steganalysis is unending. In this paper, a review report is presented for steganography and steganalysis